Makna Denotasi dan Konotasi Pada Lirik Lagu “Maafkan Aku”, "Usai", “Merasa Indah” Tiara Andini - Nensilianti; Jihan Atikah; Ridwan Ridwan (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2023)
The purpose of this study is to discuss the meaning of love which analyzes research on the lyrics of Tiara Andini's single song which has a mini album entitled "Merasa Indah", "Forgive Me", and "Usai" by utilizing Roland Barthes' semiotic hypothesis. The method used in this study is a subjective strategy. Subjective exploration is intended to understand the peculiarities of meeting test subjects, including behavior, affirmation, inspiration, and activity. The meaning of denotation and connotation is examined by Roland Barthes in relation to the meaning of "Love" in the three song lyrics in this semiotic analysis. Music is another form of art where harmonious words are used to express ideas. Semiotics is the science that is used to describe something, where language is also a blueprint of signs that contain certain messages from society. The concept of denotation and connotation was put forward by Barthes as a new definition of a sign. Signification makes the relationship between signifier and guide to the real world plausible, appearing in the intended importance, direct, and clear. In other words, denotation is a description of how signifieds and signifieds, as well as signs and objects, relate to external reality.